1989
DOI: 10.1111/j.1539-6924.1989.tb01005.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perceptions of Hong Kongese vs. Americans

Abstract: Hong Kong students rated the risk of 30 hazards and quantified a subset on six risk characteristics;data are compared to a prior study of American students. Hong Kongese rated 10 hazards substantially higher and five hazards substantially lower than Americans, and factor structures indicated differences on five hazards. Possible explanations for these differences are discussed.KEY WORDS Cross-cultural risk; risk perceptions of Hong Kongese; hazard assessment in Hong Kong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 6 publications
4
55
1
1
Order By: Relevance
“…These studies have shown that risk ratings may substantially vary from one country to another. As an example, the level of risk associated with the item "Nuclear Power Plants" was rated 31 (out of 100) in a Hungarian sample (Englander et al 1986), 34 in a Swedish sample (Nyland 1993), 47 in a Norwegian sample (Teigen et al 1988), an Australian sample (Finucane and Maybery 1996), and a Finnish sample (Mullet et al 2004), 49 in a Polish sample (Goszcynska et al 1991), 62 in an Italian sample (Savadori et al 1998), 66 in a Macanese sample (Neto and Mullet 2001) and a Brazilian sample (Nyland 1993), 67 in a Portuguese sample (Neto and Mullet 1999), 68 in a Hong Kong sample (Keown 1989), 69 in a French sample (Karpowicz-Lazreg and Mullet 1993), 72 in a U.S. sample (Slovic et al 1985) and a Korean sample (Cha 2000), 76 in an Egyptian sample (Ahmed et al 2006), 78 in a Burkina Faso sample (Koné and Mullet 1994), and 84 in a Spanish sample (Muñoz Sastre et al 2006).…”
Section: Societal Risk Perceptionmentioning
confidence: 99%
“…These studies have shown that risk ratings may substantially vary from one country to another. As an example, the level of risk associated with the item "Nuclear Power Plants" was rated 31 (out of 100) in a Hungarian sample (Englander et al 1986), 34 in a Swedish sample (Nyland 1993), 47 in a Norwegian sample (Teigen et al 1988), an Australian sample (Finucane and Maybery 1996), and a Finnish sample (Mullet et al 2004), 49 in a Polish sample (Goszcynska et al 1991), 62 in an Italian sample (Savadori et al 1998), 66 in a Macanese sample (Neto and Mullet 2001) and a Brazilian sample (Nyland 1993), 67 in a Portuguese sample (Neto and Mullet 1999), 68 in a Hong Kong sample (Keown 1989), 69 in a French sample (Karpowicz-Lazreg and Mullet 1993), 72 in a U.S. sample (Slovic et al 1985) and a Korean sample (Cha 2000), 76 in an Egyptian sample (Ahmed et al 2006), 78 in a Burkina Faso sample (Koné and Mullet 1994), and 84 in a Spanish sample (Muñoz Sastre et al 2006).…”
Section: Societal Risk Perceptionmentioning
confidence: 99%
“…Several studies have attempted to replicate or adapt the original study by Slovic, Fischhoff, and Lichtenstein (1980) in other cultures and countries, including Hungary (Englander, Farago, Slovic, & Fischhoff, 1986), Norway (Teigen, Brun, & Slovic, 1988), Hong Kong (Keown, 1989), Poland (Goszczynska, Tyszka, & Slovic, 1991), Japan (Kleinhesselink & Rosa, 1991), France (Karpowicz-Lazreg & Mullet, 1993), Italy (Savadori, Rumiati, & Bonini, 1998), Australia (Rohrmann, 1999), Vol. 8, No.…”
Section: Risk Perceptionmentioning
confidence: 99%
“…Slovic et al, 1980;Kleinhesselink & Rosa, 1991;Keown, 1989;Englander et al, 1986;and Teigen et al, 1988), this study adopted stratified sampling, ensuring representation of each of the 12 Jordanian provinces. Selecting a representative sample that included participants from different geographical locations is in line with earlier studies (e.g.…”
Section: Self-administered Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Entre dichos condicionantes los sociales, demográficos, culturales, religiosos, etc. han sido objeto de atención en trabajos como los de Fischhoff et al (1978), Gutteling y Wiegman (1993), Kleinhesselink y Rosa (1991), Keown (1989), Lai y Tao (2003). La tesis de los determinantes culturales de la percepción de los riesgos ambientales ha sido comprobada también mediante métodos no cuantitativos, tales como las entrevistas en profundidad, por ejemplo por Bax-ter y Greenlaw (2005).…”
unclassified